Characterization of the Cadherin–Catenin Complex of the Sea Anemone Nematostella vectensis and Implications for the Evolution of Metazoan Cell–Cell Adhesion - Clarke, Donald Nathaniel (Mol Biol Evol, 2016)
The cadherin–catenin complex (CCC) mediates cell–cell adhesion in bilaterian animals by linking extracellular cadherin-based adhesions to the actin cytoskeleton. However, it is unknown whether the basic organization of the complex is conserved across all metazoans. We tested whether protein interactions and actin-binding properties of the CCC are conserved in a nonbilaterian animal, the sea anemone Nematostella vectensis. We demonstrated that N. vectensis has a complete repertoire of cadherin–catenin proteins, including two classical cadherins, one α-catenin, and one β-catenin. Using size-exclusion chromatography and multi-angle light scattering, we showed that α-catenin and β-catenin formed a heterodimer that bound N. vectensis Cadherin-1 and -2. Nematostella vectensis α-catenin bound F-actin with equivalent affinity as either a monomer or an α/β-catenin heterodimer, and its affinity for F-actin was, in part, regulated by a novel insert between the N- and C-terminal domains. Nematostella vectensis α-catenin inhibited Arp2/3 complex-mediated nucleation of actin filaments, a regulatory property previously thought to be unique to mammalian αE-catenin. Thus, despite significant differences in sequence, the key interactions of the CCC are conserved between bilaterians and cnidarians, indicating that the core function of the CCC as a link between cell adhesions and the actin cytoskeleton is ancestral in the eumetazoans.